The Peculiarities of Confidence Manifestation and Psychological Conditions of its Development in the “Doctor – Patient” System - Nataliia Shevchenko; Mykhailo Sofilkanych (Проблеми сучасної психології)
The aim of the article is to present the results of empirical study on the peculiarities of the manifestation of confidence and psychological conditions of its development in the “doctor-patient” system.